2016
DOI: 10.1038/nm.4253
|View full text |Cite
|
Sign up to set email alerts
|

A chikungunya fever vaccine utilizing an insect-specific virus platform

Abstract: Traditionally, vaccine development involves tradeoffs between immunogenicity and safety. Live-attenuated vaccines typically offer rapid and durable immunity but reduced safety, while the inability of inactivated vaccines to replicate enhances safety at the expense of immunogenicity, often necessitating multiple doses and boosters. To overcome these tradeoffs, we developed the insect-specific alphavirus, Eilat virus (EILV), as a vaccine platform. To address the chikungunya virus (CHIKV) pandemic, we used an EIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
122
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 51 publications
0
122
0
1
Order By: Relevance
“…Two phase 1 clinical trials have shown a good safety and immunogenicity profile to date . A recent study that tested an insect‐specific alphavirus as the vaccine platform found promising results in mice and macaques, including immunogenicity after a single dose …”
Section: Neurological Manifestationsmentioning
confidence: 99%
“…Two phase 1 clinical trials have shown a good safety and immunogenicity profile to date . A recent study that tested an insect‐specific alphavirus as the vaccine platform found promising results in mice and macaques, including immunogenicity after a single dose …”
Section: Neurological Manifestationsmentioning
confidence: 99%
“…Several distinct vaccine approaches are currently under development, however, no vaccine has been licensed. Anti-CHIKV candidates that have been already tested in humans and/or animals include inactivated-, attenuated-, virus like particle-(VLP), DNA-and chimeric vaccines (Eckels et al, 1970;Levitt et al, 1986;Muthumani et al, 2008;Wang et al, 2008;Tiwari et al, 2009;Sharma et al, 2012Akahata et al, 2010Plante et al, 2011;Wang et al, 2011;Gorchakov et al, 2012;Brandler et al, 2013;Chang et al, 2014;García-Arriaza et al, 2014;Tretyakova et al, 2014;van den Doel et al, 2014;Erasmus et al, 2017).…”
Section: Control and Prophylaxismentioning
confidence: 99%
“…In addition to classical attenuation via serial viral passage in cells, reverse genetics strategies have been employed as platforms for construction of recombinant attenuated viruses or vaccine chimeras (Wang et al, 2008;Plante et al, 2011;Wang et al, 2011;García-Arriaza et al, 2014;van den Doel et al, 2014;Erasmus et al, 2017). An anti-CHIKV strategy involves the development of an attenuated chimeric vaccine using the Internal Ribosome Entry Site (IRES) of the Encephalomyocarditis virus (ECMV).…”
Section: Control and Prophylaxismentioning
confidence: 99%
See 2 more Smart Citations